2005
DOI: 10.1093/aob/mci081
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Account of Nectary Structure in Hexisea imbricata (Lindl.) Rchb.f. (Orchidaceae)

Abstract: Background and Aims Despite the number of orchid species that are thought to be pollinated by hummingbirds, our knowledge of the nectaries of these orchids is based solely on a single species, Maxillaria coccinea (Jacq.) L.O. Williams ex Hodge. Nevertheless, it is predicted that such nectaries are likely to be very diverse and the purpose of this paper is to compare the nectary and the process of nectar secretion in Hexisea imbricata (Lindl.) Rchb.f. with that of Maxillaria coccinea so as to begin to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 28 publications
5
68
0
3
Order By: Relevance
“…The proximity of SER and plastids were also pointed out in studies of the ultrastructure of the nectary spur of Limodorum abortivum (Pais and Figueiredo 1994) and P. bifolia (Stpiczyńska 1997). A dense osmiophilic material and tubular structures had been reported in plastids occurring in the nectaries of other orchid species (Pais and Figueiredo 1994;Stpiczyńska and Matusiewicz 2001;Stpiczyńska et al 2004Stpiczyńska et al , 2005 and from glandular trichomes involved in terpenoid synthesis (Cheniclet and Carde 1985;Turner et al 2000), in which the plastids were also in close association with ER.…”
Section: Discussionmentioning
confidence: 84%
“…The proximity of SER and plastids were also pointed out in studies of the ultrastructure of the nectary spur of Limodorum abortivum (Pais and Figueiredo 1994) and P. bifolia (Stpiczyńska 1997). A dense osmiophilic material and tubular structures had been reported in plastids occurring in the nectaries of other orchid species (Pais and Figueiredo 1994;Stpiczyńska and Matusiewicz 2001;Stpiczyńska et al 2004Stpiczyńska et al , 2005 and from glandular trichomes involved in terpenoid synthesis (Cheniclet and Carde 1985;Turner et al 2000), in which the plastids were also in close association with ER.…”
Section: Discussionmentioning
confidence: 84%
“…A observação destes compostos em maior quantidade no início da fase secretora, mostra que a planta oferece recompensa em uma forma mais energética no momento de maior suscetibilidade ao ataque de herbívoros, ou seja, quando as folhas estão em processo de expansão e diferenciação. A presença de lipídios na composição do néctar é comum e citada para nectários de diversas espécies (Baker et al 1978;Fahn 1979;1988;2000;Stpiczynska et al 2005).…”
Section: Discussionunclassified
“…ex Hayne, tais como núcleo volumoso, citoplasma denso, abundância de retículo endoplasmático, dictiossomos ativos, mitocôndrias, dentre outras, são relatadas para diversos nectários e indicativas de alta atividade metabólica (Fahn 1979;Durkee 1983;Fahn 1988;Stpiczynska et al 2005). Para Lüttge (1971), o pequeno desenvolvimento do vacuoma está relacionado ao intenso metabolismo destas células.…”
Section: Discussionunclassified
“…They contain an epidermis in addition to a nectar and a subnectary parenchyma (Stpiczy nska et al, 2005;Wist and Davis, 2006;Kaczorowski et al, 2008;Wenzler et al, 2008;Fig. 2A).…”
Section: Two Types Of Nectary Structures Harbor Unique Secretion Systemsmentioning
confidence: 99%
“…Nectaries in general consist of three components: epidermis with or without stomata or trichomes; specialized parenchyma that produces or stores nectar; and a subnectary parenchyma composed of bigger cells more loosely packed (Stpiczy nska et al, 2005;Kaczorowski et al, 2008). Detailed studies have shown that decreases in herbivory rates associated with EFN secretion result from mechanical leaf damage, jasmonic acid (JA) production, and/or volatile emission Linsenmair et al, 2001;Mathews et al, 2007;Radhika et al, 2008).…”
mentioning
confidence: 99%